A STUDY ON THE SIXTH SEMESTER STUDENTS’ OF FKIP UNIVERSITY OF RIAU ABILITY IN IDENTIFYING ENGLISH MORPHEMES - Afifah Thahirah Thahirah; Jismulatif '; Novitri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This descriptive research was conducted in order to find out the students’ ability in identifying English morphemes. The data were collected using test in the form of multiple choice. The test covered four subtopics; morphemes, allomorphs, derivation and inflection. The sample of this research was the sixth semester students of English study program of FKIP-UR who had passed content subjects English Morphology and Introduction to Linguistics. They consisted of 3 classes: A, B, and C, and using cluster sampling technique, class A was chosen as the sample of this research. Before the data were collected, the try out was conducted in order to make sure that the test was good and valid. There were 7 rejected items and those items were revised before have been distributed to the sample. From the data analysis, it was found out that the students’ ability in identifying English morphemes was in poor level with the average score 46.20. The result of the students’ ability in identifying English morphemes for each subtopic was in the average level for morphemes (50), allomorphs (52.5) and inflection (55.7) while derivation was in poor level (36.3). Based on the finding, it was suggested that the students need to do more practice in order to help increase their understanding of English morpheme. Further research can focus on studying each subtopic in details; in addition, other researchers can also focus on how to overcome the high level of difficulties of English morphology materials. Key words: Ability, Identifying, English Morphemes